Narasi Pertobatan Kolektif dalam 2 Tawarikh 12:1-12 - Anon Dwi Saputro; Endah Totok Budiyono (Te Deum (Jurnal Teologi dan Pengembangan Pelayanan), 2026)
This study aims to reconstruct the narrative and theological dimensions of 2 Chronicles 12:1–12 and to examine their relevance for a Christian leadership paradigm. While previous scholarship has highlighted the pedagogical and theological functions of Chronicles, the theme of collective repentance and its implications for Christian leadership have received comparatively limited attention. This research employs a qualitative method utilizing narrative criticism. The findings reveal a consistent narrative-theological pattern: pride leads to downfall, prophetic rebuke prompts reflection, collective repentance invites divine mercy, and communal restoration becomes the ultimate goal. This pattern underscores that Christian leadership is grounded in humility, openness to prophetic correction, and responsibility toward the community. Based on these findings, the study proposes a Chronicler’s leadership model consisting of four key elements: responsible authority, openness to prophetic rebuke, collective repentance as a response to crisis, and communal restoration as the ultimate purpose of leadership.